Bilateral acute anterior uveitis: a rare ocular side effect of erlotinib. Issue 12 (15th December 2019) - Chan, Sarah; Ahern, Elizabeth; Chaudhry, Sarah; Hughes, Brett
Abstract : Erlotinib used in the treatment of advanced non-small cell lung cancer (NSCLC) is a first-generation small-molecule tyrosine kinase inhibitor which reversibly inhibits the kinase domain of epithelial growth factor receptor (EGFR). The incidence of ocular toxicities as adverse effects (AE) of erlotinib is relatively common. However, post-marketing, acute anterior uveitis (AAU) has been reported in a small number of cases as a putative AE resulting from erlotinib therapy. We present a case of a 67-year-old, Caucasian woman, lifelong non-smoker with stage IV NSCLC who presents with decreased visual acuity and 'floaters' 6 weeks after commencing erlotinib. She was later diagnosed with erlotinib-associated bilateral AAU. This is the fifth documented case of erlotinib-associated bilateral AAU since 2010, highlighting the rarity of this AE. Thus, the possibility of AAU should always be considered in patients on EGFR-blocking therapies as significant ocular damage can occur if ophthalmic complaints are not triaged and assessed quickly.